Pengaruh Budaya Organisasi Dan Disiplin Kerja Terhadap Kinerja Karyawan (Literature Review) - Elsa Santika; Alicia Angela Yohanas; Rani Rahmadiani; Indah Rizki Maulia (Trending: Jurnal Manajemen dan Ekonomi, 2024)
The leverage of Organizational Culture and Work Discipline on Employee Performance is a scientific literature review article. The aim of writing this literature review article is to obtain a hypothesis of the influence between variables so that it can be used in further research in the realm of Performance Management. The technique used in writing articles is library research, which is obtained from online media sources such as Google Scholar and other online learning media and uses qualitative analysis techniques. The results obtained in the literature review article are: 1. Organizational culture influences employee performance; 2. Work discipline influences employee performance.